Prevention Strategies for Sexual Harassment in Academic Medicine: A Qualitative Study - Jenner, Sabine (Journal of interpersonal violence, 2022)
Sexual harassment and gendered discrimination in the workplace are global issues that can affect anyone regardless of their age, gender, job title, or field of employment. The medical field is also relevantly concerned, yet effective prevention measures are scarce. The purpose of this study was to explore preventive options for sexual harassment in an academic medical context from the employees? perspective and to develop transferable strategies. We conducted semi-structured interviews with 15 female physicians and 15 female nurses working at a tertiary referral center in Berlin, Germany, in the months of April to November 2015. The one-on-one interviews addressed the perception of sexual harassment and available and desirable preventive measures. Data were analyzed by qualitative content analysis. The participants outlined preventive measures at two levels: individual and institutional. Individual options included personal safety measures and individual protection strategies against patients, peers, and superiors. Institutional strategies included guidelines and workplace policies, structured complaint and reporting procedures, formal training options, and organizational development and leadership strategies. The current study highlights how the prevention of sexual harassment hinges on a combination of individualized and system-wide measures to capture the personal as well as the organizational dimension of sexual harassment. Only a concerted effort addressing both aspects will sensitize the workforce, support the victims, and prevent sexual harassment in medical institutions.